Integrating synchronous and asynchronous sessions in a blended writing course: Indonesian students' perspectives - Rojabi, Ahmad Ridho; Gatcho, Al Ryanne Gabonada; Croft, Sebastian Francis (ELT Forum: Journal of English Language Teaching, 2025)
In a blended writing course, synchronous and asynchronous sessions can be utilized by instructors to support students’ writing activities. Although several studies have discussed the context of blended learning (BL) in EFL or ESL context, few have specifically explored students’ perceptions of the combination of synchronous and asynchronous sessions in writing instruction. Guided by Self-Determination Theory (SDT), this study was conducted using a qualitative approach through semi-structured interviews with five students, complemented by digital record observation to enhance data triangulation, with thematic analysis undertaken to identify key findings. The results revealed that combining synchronous and asynchronous sessions in writing assignments can increase student engagement. These two types of sessions complement each other; for example, synchronous sessions allow immediate feedback that asynchronous sessions cannot provide. The recommendations from this study provide implications for developing learning strategies that integrate synchronous and asynchronous sessions in the context of writing instruction in higher education.